2010
DOI: 10.1111/j.1540-5915.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Operational Capabilities: The Secret Ingredient

Abstract: We develop a theoretical definition of operational capabilities, based on the strategic management and operations management literature, and differentiate this construct from the related constructs of resources and operational practices, drawing upon the resourcebased view of the firm as our foundation. We illustrate the key features of operational capabilities using the illustration of a restaurant kitchen. Because the traits of operational capabilities are distinct, they create a barrier to imitation, making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
260
2
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(289 citation statements)
references
References 111 publications
8
260
2
19
Order By: Relevance
“…Specifically, we study a welldocumented strategic driver of innovation performance-customer orientation-and two factors that mediate this relationship-supplier collaboration and technological capability-from the perspectives of service-dominant logic (SDL) Lusch 2004, 2008) and the resource-based view (RBV) of the firm (Barney, 1991). Previous research has indicated that customer orientation may influence innovation performance indirectly rather than directly (Keskin, 2006), whereas operational processes and capability-building activities (Peng et al, 2008;Wu et al, 2010) may facilitate the implementation of organizational strategy and thus mediate the relationship between customer orientation and innovation performance. To enable the comparison of service and manufacturing firms, innovation performance is captured by measuring the general innovativeness of each firm's offering-portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we study a welldocumented strategic driver of innovation performance-customer orientation-and two factors that mediate this relationship-supplier collaboration and technological capability-from the perspectives of service-dominant logic (SDL) Lusch 2004, 2008) and the resource-based view (RBV) of the firm (Barney, 1991). Previous research has indicated that customer orientation may influence innovation performance indirectly rather than directly (Keskin, 2006), whereas operational processes and capability-building activities (Peng et al, 2008;Wu et al, 2010) may facilitate the implementation of organizational strategy and thus mediate the relationship between customer orientation and innovation performance. To enable the comparison of service and manufacturing firms, innovation performance is captured by measuring the general innovativeness of each firm's offering-portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…According to Barney (1991), a capability is an intangible form of resource. Some researchers tend to separate capabilities from resources from a routine-based perspective (Peng, Schroeder and Shah, 2008;Wu, Melnyk and Flynn, 2010). According to Peng, Schroeder and Shah (2008, p.732), resources are "tangible and intangible firm assets that could be put into productive use".…”
Section: Dynamic Capabilities View (Dcv)mentioning
confidence: 99%
“…Our starting points are researches conducted by Flynn, Wu et al (2010), Wu, Melnyk et al (2010;, and Pavlou and El Sawy (2011). This study in regard to dimensions of OC applies the approaches proposed by their works since different labels about OC have been applied in preceding research to refer to related practices, routines, and OC, and then merged several conceptual labels from practical and theoretical reviews, and classified them to a parsimonious set in order to propose OC conceptualization, its own interpretation in this study.…”
Section: Research Model Of Operational Capabilitiesmentioning
confidence: 99%
“…15-16). Wu et al (2010) suggested operational responsiveness as the quick response to handle tangible or intangible to consistently meet customer requirements. In the context of new product development, developing software units need more immediate responses to current unexpected incidents or changing environmental work conditions to achieve efficient short-term effects with organized activities, especially, in operating process in product or service development.…”
Section: Managing Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation